RAPHANUS SATIVUS - A REVIEW OF ITS TRADITIONAL USES, PHYTOCHEMISTRY, AND PHARMACOLOGY - S, SAHA; S, PAUL; A, AFROZ; A, DEY; A, CHATTERJEE; R, KHANRA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Raphanus sativus (Radish) is a widely used vegetable belonging to the family Brassicaceae, generally grown as annual or biennial plants, with a taproot which is much enlarged when it is cultivated. In Yemenite folk medicines, R. sativus juice is used in eliminating kidney stones. Few people, specifically in the Middle East, prefer to drink its juice in pursuit of certain health benefits. In Unani, Greeko-Arab, and Indian folk medicine, It is used as a home remedy for the treatment of many diseases such as jaundice, gallstone, liver diseases, rectal disorder, indigestion, and other gastric pains. This article has reviewed the information available on R. sativus ethnopharmacology, geographical distribution, chemical composition, and pharmacological uses. The information on botanical description, distribution, traditional uses, chemical composition, bioactive components, and therapeutic investigations was gathered from a comprehensive literature search of electronic databases such as Science Direct, PubMed, Web of Science, Wiley, ACS, Springer, Google Scholar, and SCOPUS until 2020 for publications. An elaborative study has been done on botanical characterization, traditional uses, chemical composition, and various pharmacological or therapeutic uses. Mainly this plant is fully loaded with polyphenolic compounds which exert a promising antioxidant property. This plant possesses various therapeutic benefits such as anti-inflammatory, anti-microbial, anti-tumorogenesis, anti-cancer, anti-diabetic, and anti-nephrotoxicity activity. The comprehensive literature analysis shows that a wide range of populations has utilized various parts of R. sativus around the globe. The above information shows that the plant holds a variety of hidden and unknown potentials which can be studied extensively for its phytoconstituents and therapeutic outcomes. However, while searching through the literature available, it was observed that there is a lack of information on its phytochemical profiling and its corresponding pharmacological benefits. It is believed that this review will help lay the groundwork for encouraging pharmacological and pharmaceutical studies.